Bioremediation of Diesel Contaminated Marine Water by Bacteria: A Review and Bibliometric Analysis - Khalid, Farah Eryssa; Lim, Zheng Syuen; Sabri, Suriana; Gomez Fuentes, Claudio German; Zulkharnain, Azham; Ahmad, Siti Aqlima (My University, 2021)
T Oil pollution can cause tremendous harm and risk to the water ecosystem and organisms due to the relatively recalcitrant hydrocarbon compounds. The current chemical method used to treat the ecosystem polluted with diesel is incompetent and expensive for a large-scale treatment. Thus, bioremediation technique seems urgent and requires more attention to solve the existing environmental problems. Biological agents, including microorganisms, carry out the biodegradation process where organic pollutants are mineralized into water, carbon dioxide, and less toxic compounds. Hydrocarbon-degrading bacteria are ubiquitous in the nature and often exploited for their specialty to bioremediate the oil-polluted area. The capability of these bacteria to utilize hydrocarbon compounds as a carbon source is the main reason behind their species exploitation. Recently, microbial remediation by halophilic bacteria has received many positive feedbacks as an efficient pollutant degrader. These halophilic bacteria are also considered as suitable candidates for bioremediation in hypersaline environments. However, only a few microbial species have been isolated with limited available information on the biodegradation of organic pollutants by halophilic bacteria. The fundamental aspect for successful bioremediation includes selecting appropriate microbes with a high capability of pollutant degradation. Therefore, high salinity bacteria are remarkable microbes for diesel degradation. This paper provides an updated overview of diesel hydrocarbon degradation, the effects of oil spills on the environment and living organisms, and the potential role of high salinity bacteria to decontaminate the organic pollutants in the water environment.
Keywords: diesel; water pollution; bioremediation; organic pollutants; halophilic bacteria